The impact of credibility of influencers recommendations on social media on consumers behavior towards brands : Utjecaj vjerodostojnosti preporuka influencera na društvenim mrežama na ponašanje potrošača prema markama - Kwiatek, Piotr (Array, 2021)
Companies are becoming increasingly aware of the importance and opportunities provided by social media in order to communicate faster and more efficiently with their consumers. In order to convey the message about the value of their brands to their target market, organizations hire influential people who are considered to be the creators of public opinion in a virtual environment. Nowadays, social media are crowded with micro and macro influencers, or at least those who present themselves as such. Their main job is to represent and recommend brands to other users (their followers) and thus influence consumer attitudes about brands and possibly strengthen their purchasing decisions. Very often, influencers on social media are hired by companies to promote their brands for a fee. In order to have more control over their communication activities, companies provide them, in advance, with the content they want to be conveyed to consumers, but also the time frame when the message should be launched. In this way, organizations try to reduce the risk of turning electronic word-of-mouth (EWOM) communication into a negative one. In order for consumers to trust the recommendations of influencers on social media, these people need to have significant expertise in a certain area, charisma and respect from other users, so that their credibility affects the value of content and recommendations they place in the online environment. The aim of this paper is to present the attitudes of respondents who use social media websites about the impact of the credibility of influencers' recommendations on social media, and their opinion on whether and in what way their credibility influences consumer attitudes towards brands.